Periphytic diatom as bioindicators in urban and rural streams - doi: 10.4025/actascibiolsci.v36i1.18175 (Acta Scientiarum. Biological Sciences, 2013)
Periphytic diatoms were sampled from two streams, one located in an urban area and the other located in a rural area, in Maringá, State of Paraná, Brazil. In addition to temporal variability, differences in the assemblage structure between streams were evaluated and correlated with physical and chemical characteristics. Six samples of periphytic diatoms were collected from each stream from July 2007 to June 2008. The streams differed in abiotic factors and in relation to the structure of diatom assemblages and the spatial scale was more important than the temporal scale (ANOVA, p â‰¥ 0.05; non-metric multidimensional scaling (NMS) stress = 13.73, p = 0.009). The Procrustes analysis (m2 = 0.7607 and p = 0.0001) showed that variables with the greatest influence on the assemblage structure of diatoms were total nitrogen (TN), electrical conductivity, dissolved oxygen (DO), chemical oxygen demand (COD), biochemical oxygen demand (BOD5) and flow. These results indicate that abiotic variables modified by the land-use had greater influence on the community structure of diatoms than seasonal changes in abiotic variables.